MODELLING OF THE GAS DIFFUSION IN FLEXIBLE PIPELINES FOR OIL & GAS PRODUCTION - Marius STAN (Fiabilitate şi Durabilitate, 2017)
This presentation describes a model used to study gas diffusion through layers of flexible pipes by time. The temperature gradient pipe is considered as temperature dependent permeability rates. This model is coupled with a calculation that indicate changes in pressure and volume of vapors resulting in the annular space. Associated mathematical models and methods for solving the results obtained are presented in Math Soft with a user-friendly interface that helps in data entry and processing results. In this presentation will show the possibilities of this software.